FROM CUBICLES TO CLOUDS: ANALYZING OPERATIONAL EXPENDITURES IN THE ERA OF REMOTE WORK FOR IT COMPANIES - Kumar, Rekha; Kolte, Ashutosh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The global shift toward remote work has significantly altered operational dynamics within the information technology (IT) sector. This paper examines the impact of remote working on the operational costs of IT companies, with a specific focus on changes in facilities costs, employee benefits, and other administrative expenses. Utilizing a comparative approach, the study collects quantitative data from financial reports of selected IT companies. Preliminary findings suggest that remote work has led to a reduction in direct office-related expenses but has introduced new costs related to digital infrastructure and cybersecurity. The research also explores the long-term implications of these shifts, including potential savings from reduced real estate investments and increased expenditures on virtual collaboration tools. By analyzing these trends, this paper aims to provide a comprehensive overview of cost heads and find if these are affected by the work-from-home (WFH) operating model in the IT industry, offering valuable insights for policymakers and corporate leaders as they strategize future working models.